Two decades taken at speed: genomics, cell biology, ecology, and evolution of protists - Dacks, Joel B; Ginger, Michael L (BMC biology, 2023)
In dynamic scientific fields, two decades can be an eternity, with technical and conceptual advances leading to drastically changed landscapes and paradigms. Noted natural philosopher Ferris Bueller once opined, “Life moves pretty fast. If you don’t look around once in a while, you could miss it”, and at the 20-year anniversary ofBMC Biology, it is worth a “look around” at the field of evolutionary protistology. Things look quite differently today than they did whenBMC Biology was founded.
Keywords: ekologie; Genomics; Ecology; biologická evoluce; Biological Evolution; genomika; Eukaryota